A bilingual advantage in how children integrate multiple cues to understand a speaker's referential intent*. Issue 3 (July 2015) - YOW, W. QUIN; MARKMAN, ELLEN M.
<x content-type="archive" xml:space="preserve">Abstract</x> In everyday communication, speakers make use of a variety of contextual and gestural cues to modulate the meaning of an utterance. Young children have difficulty in integrating multiple communicative cues when some of them have to be interpreted differently depending on other co-occurring cues. However, bilingual children, who regularly experience communicative challenges that demand greater attention and flexibility, may be more adept in integrating multiple cues to understand a speaker's communicative intent. We replicated Nurmsoo and Bloom's (2008) procedure with three-year-old monolingual and bilingual children using a procedure in which they saw two novel objects while the experimenter could see only one. The experimenter looked at the object she could see and said either "There's the [novel-word!]" or "Where's the [novel-word]?". Compared to monolinguals, bilingual preschoolers were better able to integrate the semantics of "where", perceptual access of the experimenter, and the nonlinguistic context of the game to successfully differentiate the speaker's communicative intent.